1975
DOI: 10.2337/diab.24.9.785
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Ketosis

Abstract: Twenty-four chronic alcohol abusers hospitalized during a twenty-seven-month period were suspected of having "alcoholic ketoacidosis" because they had ketonuria or ketonemia with little or no glucosuria. Twenty-one had moderate or severe ketosis, with plasma 3-hydroxybutyrate of 5.2 to 22.5 mmol/L. Fifteen of this group were not diabetic, while six were later found to have mild postprandial hyperglycemia without glycosuria. Three patients who had continued to drink until shortly before admission, though at fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 0 publications
3
32
0
3
Order By: Relevance
“…However, in the series presented by Fulop et al 1 and Halperin et al 2 and in the present case, the lowest pH values (57¢28) were associated with the highest concentrations of b-hydroxybutyrate and lactate (415 mmol/ L). Moderately raised ketone concentrations (510 mmol/ L) were associated with normal or slightly below normal pH values.…”
Section: Discussionsupporting
confidence: 42%
“…However, in the series presented by Fulop et al 1 and Halperin et al 2 and in the present case, the lowest pH values (57¢28) were associated with the highest concentrations of b-hydroxybutyrate and lactate (415 mmol/ L). Moderately raised ketone concentrations (510 mmol/ L) were associated with normal or slightly below normal pH values.…”
Section: Discussionsupporting
confidence: 42%
“…Patients with chronic ethanol abuse with a recent binge culminating in nausea, vomiting, and acute starvation may present with alcoholic ketoacidosis (AKA). In virtually all reported series of AKA, the elevation of total ketone body concentration DIABETES CARE, VOLUME 24, NUMBER 1, JANUARY 2001 139 (7-10 mmol/l) is comparable to that reported in patients with DKA (161,162). However, in in vitro studies, the altered redox cellular state in AKA caused by an increased ratio of NADH to NAD levels leads to a reduction of pyruvate and oxaloacetate, which results in impaired gluconeogenesis (163).…”
Section: Differential Diagnosismentioning
confidence: 83%
“…Ball et al [71] reported a patient with combined ketoacidosis and lactic acidosis whose ratio was 22.4 (9.9/0.4 mmol/1). Fulop and Hoberman [72] described a patient with alco holic ketoacidosis who had a negative serum Acetest reaction despite a plasma P-OHB level of 12.9 mmol/1. Likewise, 2 of the 5 patients of Levy et al [74] with alco holic ketoacidosis had negative tests for urinary and se rum ketones, and in the series of 30 cases of alcoholic ke toacidosis recently reported by Soffer and Hamburger [73], most patients had negative reactions.…”
Section: Fi-hydroxybutyric Acidosismentioning
confidence: 99%
“…Rather, the intracellular ratios of both lactate/pyruvate and P-OHB/AcAc are influenced coterminously by the redox state. Nevertheless, because the latter ratio is directed pri marily by intramitochondrial events, and the former by changes in the extramitochondrial compartment, the ab sence of a close correlation between the serum concentra tions of P-OHB and lactate is not surprising [42], The p-OHB/AcAc ratio in DKA is typically about 3 to 1, but several clinical reports documenting the finding of negative or weakly positive tests for blood and/or urinary ketones, despite pronounced acidosis [36,37,67,[72][73][74], suggest that P-OHB/AcAc ratios sometimes exceed 10 to 1. Alberti and Ilockaday [24], in a study of 50 patients with diabetic coma and precoma, emphasized that al though the mean P-OHB/AcAc ratio was 5.2, the individ ual values ranged from 1.9 to as high as 31.7.…”
Section: Fi-hydroxybutyric Acidosismentioning
confidence: 99%